Quantification of rifampicin loaded into inhaled polymeric nanoparticles by reversed phase high-performance liquid chromatography in pulmonary nonphagocytic cellular uptake - Scolari, Ivana Romina (2024)
Rifampicin is an antibiotic effective against both Gram-negative and Gram-positive bacteria and is commonly used as a first-line treatment for tuberculosis caused by Mycobacterium tuberculosis. In this study, a reversed-phase high-performance liquid chromatography method was developed and validated to assess rifampicin, either free or combined with ascorbic acid, loaded into chitosan/Tween 80-coated alginate nanoparticles. The method utilized a reversed-phase C18 Restek column with specific chromatographic conditions: a mobile phase of 60 : 40 ratios of methanol/buffer phosphate (pH 7.0), at a flow rate of 0.8 mL min−1, and an injection volume of 15 μL. rifampicin and the internal standard (rifamycin) had retention times of 4.0 and 2.5 min, respectively, and were detected at 334 nm. The method demonstrated the stability of stored samples after freezing–thawing cycles and specificity for rifampicin, even in the presence of degradation products from stress conditions. The high-performance liquid chromatography method was found to be specific, precise, robust, and sensitive. Results indicated that rifampicin accumulation and uptake kinetics varied based on cell type, formulation (free or loaded in nanoparticles), rifampicin concentration, and incubation time. Confocal fluorescence microscopy images supported these findings, showing isothiocyanate fluorescein nanoparticles distribution in different intracellular regions depending on the cell type used. The societal impact of this research lies in its potential to advance the treatment of respiratory infectious diseases, such as tuberculosis, through the development of more effective and specific drug delivery methods. By optimizing the way drugs, particularly rifampicin in this case, interact with lung cells, we aim to achieve greater treatment efficacy and alleviate the overall burden of disease. Furthermore, our study offers novel insights into the intracellular behavior of rifampin from polymeric nanoparticles, paving the way for personalized medicine approaches in the treatment of respiratory infections. This dual focus on social impact and innovation underscores our commitment to improving global health outcomes and addressing pressing public health challenges.